Upregulation of mitochondrial function is associated with advanced prostate cancer - Valentin Baumgartner; Thomas Paul Scherer; Ashkan Mortezavi; Niels Rupp; Holger Moch; Peter Wild; Susanne Dettwiler; Miriam Wanner; Dominik Enderlin; Souzan Salemi; Daniel Eberli (Advances in Cancer Biology - Metastasis)
1 Abstract: Background: The mitochondrial metabolism in prostate cancer (PCa) is of great importance due the unique metabolic shift from glycolysis to oxidative phosphorylation. In this study, we aimed to analyze the expression level of mitochondrial markers TOM20, DRP1 and OPA1 in benign and malignant tissue, to assess if these markers are associated with different grade and stage of PCa. Materials and methods: This study assessed TOM20, DRP1, and OPA1 expression in formalin-fixed, paraffin-embedded prostate tissue samples, including benign and malignant tissue specimen. Immunohistochemistry on tissue microarrays was conducted, with staining intensities scored semi-quantitatively. Statistical analyses evaluated associations with PCa grade and stage. A survival analysis for biochemical recurrence (RFS), overall survival (OS) and disease specific survival (DSS) was performed using multivariate Cox regression analysis to assess prognostic properties of the markers. Results: In total, 527 patients were included in our analysis, which composed of 45 (8.5 %) benign prostate hyperplasia (BPH) and 482 (91.5 %) PCa samples (436 localized (90.5 %) and 46 (9.5 %) metastatic). Immunoreactivity for TOM20, DRP1 and OPA1 was strong in 2 of 43 (4.7 %), 1 of 43 (2.3 %) and 0 of 43 (0 %) of BPH control tissue. Strong marker expression was significantly increased in radical prostatectomy specimen (TOM20: 111/371 (29.9 %), DRP1: 89/373 (23.9 %), OPA1: 60/371 (16.2 %), p < 0.001) and in metastatic tissue (TOM20: 22/42 (52.4 %), DRP1: 14/42 (33.3 %), OPA1: 21/41 (51.2 %), p < 0.001). None of the markers demonstrated prognostic properties for RFS, OS, and DSS. Conclusion: A strong association between the expression of the mitochondrial markers TOM20, DRP1 and OPA1 and PCa aggressiveness was demonstrated. However, these markers were not found to be prognostic regarding RFS, OS and DSS. Future studies are needed focusing on the underlying mechanisms of the upregulation of mitochondrial metabolism in aggressive PCa and evaluate potential therapeutic implications.